1995
DOI: 10.1007/bf02282909
|View full text |Cite
|
Sign up to set email alerts
|

Variable response of the Mongolian gerbil to unilateral carotid occlusion: Magnetic resonance imaging and neuropathological characterization

Abstract: In the present investigation, we estimated both the evolution and the severity of ischemic damage following unilateral carotid occlusion (UCO) in Mongolian gerbils by using conventional magnetic resonance imaging (MRI, i.e. T2 weighted imaging) and histological techniques. Immediately after UCO, the animals showed different clinical effects. The mortality (46%) detected within the first 48h was considered an "stroke-sensitivity", the "stroke-resistant" animals showed wide variability in terms of both temporal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Studies in gerbils have identified abnormal GABAergic dependent synaptic transmission as an important underlying mechanism of seizures [41][42][43]. Investigations using gerbils as a stroke model have shown that "stroke-prone" and "stroke-resistant" gerbils are associated with the conditions of posterior communicating arteries in the circle of Willis [44][45][46][47][48]. In addition, the gerbil has been commonly used for studying a number of parasitic, viral and bacterial diseases [reviewed in 2].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in gerbils have identified abnormal GABAergic dependent synaptic transmission as an important underlying mechanism of seizures [41][42][43]. Investigations using gerbils as a stroke model have shown that "stroke-prone" and "stroke-resistant" gerbils are associated with the conditions of posterior communicating arteries in the circle of Willis [44][45][46][47][48]. In addition, the gerbil has been commonly used for studying a number of parasitic, viral and bacterial diseases [reviewed in 2].…”
Section: Introductionmentioning
confidence: 99%
“…The mortality in this model reflects the severity of the injury, and it is an important variable in assessing drugs for the treatment of ischemia. In this model, mortality rates between 30 and 40% at 24 and 48 hours after ischemia have been reported [41, 42]. This allows us to suggest that these animals have a cognitive dysfunction induced by ischemia, which affected their learning and short-term memory [43].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon can be caused by the interaction of polymer with one or more ingredients of the artery has been used for studying the physiopathology of the brain ischemia and for the evaluation of putative neuroprotective agents. In this model, a mortality rate from 25 to 50% has been reported [44,45].…”
Section: Formulation Preparationsmentioning
confidence: 99%